Birodalmi térszerkezetek a Kárpát-medencében: a Római Birodalomtól az Oszmán Birodalom kiűzéséig - Csüllög, Gábor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
In Europe’s history can be found local states and empires, but their proportion and their political role were changing in the thousand years. The historical geographical research of the state spaces of the empires concentrates on the spatiality (flow lines, flow junctions, conquest of sate spaces, turning conquered state spaces into a province). The Carpathian Basin is the great area of Europe, and has been a contact and mixing region of ethnic, cultural and economic influences for thousands of years and where serious state spaces came into existence already in the first century in the flow zone along Danube. But not only the Roman one, the Ottoman one and Habsburg state can be considered for an empire but tak-ing the spatial structure into consideration the medieval Hungarian state, so the imperial structures cover the area’s history because of this from the Roman Empire until the 20th century.